Effect of iron on enamel demineralization and remineralization in vitro - Ribeiro Pinto Alves, Karina Mirela [UNESP]; Franco, Karina Simoes [UNESP]; Sassaki, Kikue Takebayashi [UNESP]; Rabelo Buzalaf, Marilia Afonso; Delbem, Alberto Carlos Botazzo [UNESP] (Pergamon-Elsevier B.V. Ltd, 2011)
Objective: To evaluate the effect of ferrous sulphate on enamel demineralization and remineralization, using pH-cycling models.Design: Fifty blocks were selected by their initial surface hardness and subjected to a pH-cycling demineralization process. Artificially demineralized lesions were produced in 60 blocks; out of these blocks, the surface hardness of 50 blocks and the cross-sectional hardness of 10 blocks were determined. The 50 blocks were then subjected to a remineralization pH-cycling process. Treatments were carried out using ferrous sulphate solutions of different concentrations (0.333, 0.840, 18.0, and 70.0 mu g Fe/mL) and a control group (deionized water). The final surface hardness (SH(2)) was determined, and the integrated subsurface hardness (Delta KHN) was calculated. The enamel blocks were analysed for fluoride, calcium, phosphorus, and iron. The obtained data were distributed heterogeneously and were analysed using the Kruskal-Wallis test (p < 0.05).Results: In demineralization pH cycling, the group treated with the 18.0 mu g Fe/mL solution had higher secondary surface hardness and lower integrated subsurface hardness (Delta KHN) than the other groups. In remineralization pH cycling, the control group showed the lowest value of Delta KHN. A decline in Ca and P concentration was observed when the Fe concentration increased (p < 0.05). There was no significant difference in the F concentration (p > 0.05) and an increase in Fe concentration (p < 0.05) in the enamel was observed when the Fe concentration increased in both the demineralization and remineralization experiments.Conclusion: The results suggest that iron reduces demineralization but does not allow remineralization to occur. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Iron; Dental enamel; Tooth demineralization; Tooth remineralization; Hardness